Worldwide Assessment of the Root and Root Canal Characteristics of Maxillary Premolars - A Multi-center Cone-beam Computed Tomography Cross-sectional Study With Meta-analysis - Martins, Jorge N R; Versiani, Marco A (Journal of endodontics, 2024)
This worldwide study examined the root and root canal characteristics of maxillary premolars and explored how demographic factors impact the outcomes. Observers from 44 countries assessed 26,400 maxillary premolars using cone-beam computed tomography and employed a standardized screening method to gather data on multiple canal morphology and 3-rooted configuration (primary outcomes), as well as secondary outcomes related to root and root canal anatomies. Demographic factors such as ethnicity, sex, and age were collected for each participant. The intra- and inter-observer tests ensured observer reliability. Primary outcomes were represented as odds ratios and untransformed proportions accompanied by 95% confidence interval (CI) forest plots. Meta-analysis compared sub-groups and identified sources of heterogeneity (α = 5%). The overall prevalence of multiple canal morphology in the first premolar was 93.5% (95% CI, 93.3%-94.7%), while in the second premolar, it was 49.7% (95% CI, 44.9%-54.6%). The proportion of 3-rooted configuration was 1.8% (95% CI, 1.4%-2.1%) in the first premolar and 0.4% (95% CI, 0.3%-0.5%) in the second. Asian countries generally displayed fewer roots and root canals, while European nations showed higher counts (P < .05). Males exhibited higher percentages and odds ratios for both outcomes in both premolars. Younger patients demonstrated lower percentages of multiple root canal morphologies (P < .05). Factors such as tooth side, voxel size and field-of-view did not influence the outcomes (P > .05). The worldwide assessment of root and root canal characteristics of maxillary premolars has revealed a discernible influence of various factors such as tooth type, geographical region, ethnicity, sex, and age.